The Position, Election and Powers of the President of the Republic of Estonia (Lex localis - Journal of Local Self-Government, 2009)
Estonia has a typical parliamentary system in which the President of the Republic is indirectly elected. This paper deals with the position of the President of the Republic of Estonia, with the election of the President, and with his powers. Particular attention is paid to standard functions and powers in the legislative and executive realms. In addition, the extraordinary powers of the President of the Republic are also mentioned. The largest chapter of this paper describes the election of the President of the Republic. The Estonian regulation is specific because it allows up to five rounds of elections. The President of the Republic is elected by the Parliament in the first three rounds of elections. If no candidate receives a majority of votes, a special electoral body is formed (it is made up of the Members of Parliament and the representatives of local self-governing communities) to elect the President of the Republic in the fourth round of elections and, if necessary, in the fifth round of elections. The local council of each local community elects at least one representative to this body. The number of the representatives an individual local community will have depends on the number of citizens living in its area. In the end, the paper presents the responsibilities of the President of the Republic.KEY WORDS: • electins • President of the Republic of Estonia • local self-government • parliament • Estonia